Pengaruh Media Digital dalam Penggunaan Media Sosial Terhadap Pola Komunikasi Interpersonal pada Remaja - Alaika Amaly Khaira; Gisella Aisyah; Hocky Nis Kharisma Dewi; Rahma Aniq Aulia; April Laksana (Institut Nalanda, 2024)
Digital media has a role in establishing two-way communication. Two-way communication itself consists of several factors, one of which is the influence of digital media on interpersonal communication, highlighting the challenges and opportunities that arise. Technological transformations, especially social media, have changed the way individuals interact, creating global connectivity but also reducing emotional engagement and depth of relationships. This research found that although digital media facilitates greater interaction, there are risks to the quality of communication and social skills. Therefore, it is important to manage the use of digital media in order to maintain the quality of effective interpersonal communication. This study focuses on the realm of interpersonal communication, specifically examining the effects of social media on the interpersonal communication of adolescents. The objective is to assess how social media impacts these interactions. The methodology employed is qualitative, with data gathered through literature review and comprehensive interviews with a select group of teenagers. The analysis of qualitative data is an interactive process that begins at the early stages of research and continues until results are obtained. Findings indicate that social media usage does influence the interpersonal communication of teenagers, potentially leading to a decrease in direct interactions and a possible desensitization to real-world situations. It is imperative, therefore, that teenagers are provided with exemplary models of communication.